Application of rock mass classification and Blastability Index for the improvement of wall control: a hard-rock mining case study - Segaetsho, G. S. K.; Zvarivadza, Tawanda (Journal of the Southern African Institute of Mining and Metallurgy, 2021)
Conventional blasting rules of thumb used to develop blast designs are based on parametric ratios, with insufficient consideration of the rock mass factors that influence the achievability of final wall designs. At a hard-rock mine in Botswana, catchment berm designs were frequently unachievable, which exposed the mining operation to safety hazards such as local wallrock failure from damaged crests, frozen toes, and rolling rockfalls from higher mining levels. Increased standoff distances from the highwall reduced the manoeuvring area on the pit floor and the extraction factor that was safely achievable. Application of rock mass classification and the Blastability Index (BI) as a means to improve wall control was investigated. Zones were defined according to rock types forming the western highwall rock mass, and distinguishing rock mass classification factors were used to establish the suitable wall control designs. The approach combined rock mass classification methodologies such as the Geological Strength Index and the Rock Mass Rating, and related them to the BI and discontinuities of the rock mass to produce a design input tool that can be used to develop objective wall control designs. The designs driven by the tool inherently take into account the rock mass characteristic factors at the centre of the rock mass classification methods mentioned above, and significantly reduce the dependence on rules of thumb. It was found that this approach produces designs with explosive energy measures that are consistent with the required rock-breaking effort and the behaviour of discontinuities, while preserving perimeter walls.